High power testing of water-cooled waveguide for ITER-like ECH transmission lines. (30th March 2017) - Anderson, J.P.; Doane, J.L.; Grunloh, H.J.; O'Neill, R.C.; Ikeda, R.; Oda, Y.; Takahashi, K.; Sakamoto, K.
Abstract: The results of high power testing of new water-cooled ECH waveguide components for ITER are presented. The components are a precision-coupled 4.2 m waveguide assembly, a short expansion joint, and water-cooled waveguide for gyrotron commissioning. The testing was conducted at the QST Naka Fusion Institute using gyrotron pulses of 450 kW at 170 GHz for 300 s. Analysis shows that the power absorbed per unit length for the various waveguide components are dependent on location in the transmission line with respect to high order mode generators, such as miter bends. Additionally, larger-than-expected reflections from the load led to high absorption levels in the transmission line.